Infection in elderly interned in long-term care facilities - Fortes Villas Boas, Paulo Josi [UNESP]; Dos Anjos Ferreira, Ana Lucia [UNESP] (Assoc Medica Brasileira, 2007)
OBJECTIVE. To evaluate the occurrence of infection in elderly interned in long-term care facilities (LTCF) during 13 consecutive months. METHODS. Fifty five elderly were evaluated according to infection and, reporting was standardized. RESULTS. The median age was 75 (66 - 81) years. The data set consisted of 20,896 patients-day (PD) of core during the period, with a total of 76 infections for a pooled mean rote of infections 3.20 per 1,000 PD of core. Patient infection rote was 63.6%. Prevalent topographies of infection were respiratory (50%), urinary tract 32%), skin and soft tissue (12%) end gastroenteritis (7%), with on infection rote for specific categories/1000 PD of 1.60, 1.01, 0.38, 0.21, respectively. Mortality infection rote was 5%. Microbiological agents were isolated in 30.5% of the infection episodes. Escherichia coli and Staphylococcus aureus were prevalent. CONCLUSION. Infection presented on elevated incidence in the elderly interned, but no unusual problem with infections was disclosed.
Keywords: elderly; infection; epidemiology; long-term care facilities